Odpowiedzi

2010-03-25T18:56:24+01:00
A) 0= 3-(2x + 1)
0= 3-2x-1
2x= 3-1
2x= 2/2
x=1

b) 0= (x-1)-(3x-5)
0= x-1-3x+5
3x-x=5-1
2x=4/2
x=2

c) 3(1-x)-(1-2x) = 9
3-3x-1+2x=9
-3x+2x=9+3
-x=12/ (-1)
x=-12
1 5 1
2010-03-25T18:58:36+01:00
A) 0 = 3 - (2x + 1)
b) 0= (x - 1) - (3x -5 )
c)3 (1 - x) - (1 - 2x) = 9

a) 0= 3-(2x + 1)
0= 3-2x-1
2x= 3-1
2x= 2/2
x=1

b) 0= (x-1)-(3x-5)
0= x-1-3x+5
3x-x=5-1
2x=4/2
x=2

c) 3(1-x)-(1-2x) = 9
3-3x-1+2x=9
-3x+2x=9+3
-x=12/ (-1)
x=-12
2010-03-25T19:02:24+01:00
A)0 = 3-(2x + 1)
0 = 3 - 2x + 1
2x = 3 + 1 - 0
2x=4/:2
x = 2

b)0 =(x-1)-(3x-5)
0=z-1-3x-5-0
-x+3x=-1-5-0
2x=6/:2
x=3

c)3(1-x)-(1-2x)=9
3-3x-1-2x=9
-3x-2x=9+1-3
5x=7/:5
x=1,4